Introduction of macarpine as a novel cell-permeant DNA dye for live cell imaging and flow cytometry sorting - Slaninová, Iva; López-Sánchez, Noelia; Šebrlová, Kristýna; Vymazal, Ondřej; Frade, José María; Táborská, Eva (Biology of the cell, 2016)
BACKGROUND INFORMATION: Macarpine (MA) is a quaternary benzophenanthridine plant alkaloid isolated from Macleaya microcarpa or Stylophorum lasiocarpum. Benzophenanthridine alkaloids are interesting natural products that display antiproliferative, antimicrobial, antifungal and anti-inflammatory activities, and also fluorescence properties. In a previous study, we demonstrated that thanks to its ability to interact with DNA and its spectral properties MA could be used as a supravital DNA probe for fluorescence microscopy and flow cytometry including analyses of the cell cycle. In this study, we evaluated the suitability of MA as a DNA dye for time-lapse microscopy and flow-cytometric cell sorting. RESULTS: Living A-375 and MEF cells stained with MA were monitored by time-lapse microscopy for 24 h. Mitoses were observed at MA concentrations up to 0.5 μg/ml during the first 2-3 h. After this period of time, cells treated with MA at concentrations of 0.75 and 0.5 μg/ml underwent apoptosis. Cells cultivated with MA at concentration of 0.25 μg/ml or lower survived throughout the 24 h period. Toxicity of MA was dependent on light wavelength and frequency of image capturing. The intensity of MA fluorescence decreased during the incubation. MA concentration of 0.1 μg/ml was identified as the most suitable for live cell imaging with respect to fluorescence intensity and toxicity. MA at the concentration 10 μg/ml was used for sorting of enhanced green fluorescent protein (EGFP)-labelled neurons and fibroblasts yielding profiles similar to those obtained with DRAQ5. Contrary to DRAQ5, MA-stained cells survived in culture, and the sorted cells lost the MA signal suggesting reversible binding of the dye to the DNA. CONCLUSION: The results proved that MA may readily be used for chromosomes depicting and mitosis monitoring by time-lapse microscopy. In addition, MA has shown to be a suitable probe for sorting of EGFP-labelled cells, including neurons, that survived the labelling process. SIGNIFICANCE: In consideration of the results, we highly anticipate an onward use of MA in a broad range of applications based on live cell sorting and imaging, for example, cell synchronisation and monitoring of proliferation as an important experimental and/or diagnostic utility.
Keywords: Green Fluorescent Proteins; Fluorescent Dyes; Microscopy, Fluorescence; průtoková cytometrie; Cell Cycle; DNA; lidé; Flow Cytometry; fluorescenční barviva; fluorescenční mikroskopie; buněčný cyklus; zelené fluorescenční proteiny; separace buněk; Benzophenanthridines; benzofenantridiny; Cell Separation; buněčné kultury; Cell Survival; Cell Culture Techniques; viabilita buněk; Humans